Pengaruh Inovasi, Promosi, Kualitas Produk, Harga Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Produk Starbucks - Fika Nur Auliya; Sutarmin Sutarmin (Jurnal Visi Manajemen, 2025)
Customer satisfaction is very important for the continuation of a business because customer satisfaction can influence customer perspectives on products and services. The phenomenon that occurred in this study was a decrease in the market share of starbucks products in 2021-2023. The purpose of this study was to analyze the effect of innovation, promotion, product quality, price and service quality on customer satisfaction. This research was conducted on consumers of starbucks products in the Indonesian region. The data used in this study are primary data obtained from distributing questionnaires to respondents using google form. Data analysis in this study used multiple linear regression with the help of SPSS software version 26. The sample in this study were 97 respondents. The sampling technique used probability sampling with accidental sampling method. The results of this study explain that 1) innovation has a positive effect on customer satisfaction 2) promotion has a positive effect on customer satisfaction 3) product quality has no effect on customer satisfaction 4) price has a positive effect on customer satisfaction 5) service quality has a positive effect on customer satisfaction.